The influence of bank-firm loan network structure on systemic risk: from the perspective of complex networks - Li, Zhengyong; Fu, Deyin; Li, Haiting (Frontiers in Physics, 2025)
The structure of the bank-firm loan network is crucial for understanding the transmission of systemic risk within the banking system. Drawing on complex network theory, this study analyzes loan data from 370 Chinese commercial banks spanning January 2013 to December 2023 to construct a syndicated loan network, wherein different banks lend to the same enterprise. This analysis reveals how the structure of this network influences systemic risk in the banking sector across various periods. Our findings indicate that, in the long term, network density and centralization significantly mitigate systemic risk, whereas transitivity and average clustering coefficients have a positive effect on systemic risk. In the short term, the network demonstrates strong mean-reverting properties. Additionally, we observe a noteworthy phenomenon: the bank-firm loan relationships exhibit a ‘core-periphery’ hierarchical structure, characterized by a network that is both robust and fragile. These insights offer a novel perspective on the relationship between bank network structures and systemic risk, contributing to the interdisciplinary application of physics in economic and financial studies.